Effects of Trichoderma viride chitinases on the peritrophic matrix of Lepidoptera. Issue 5 (10th August 2015) - Berini, Francesca; Caccia, Silvia; Franzetti, Eleonora; Congiu, Terenzio; Marinelli, Flavia; Casartelli, Morena; Tettamanti, Gianluca
Abstract: BACKGROUND: The peritrophic matrix (PM) is formed by a network of chitin fibrils associated with proteins, glycoproteins and proteoglycans that lines the insect midgut. It is a physical barrier involved in digestion processes, and protects the midgut epithelium from food abrasion, pathogen infections and toxic materials. Given its fundamental role in insect physiology, the PM represents an excellent target for pest control strategies. Although a number of viral, bacterial and insect chitinolytic enzymes affecting PM integrity have already been tested, exploitation of fungal chitinases has been almost neglected. Fungal chitinases, already in use as fungal phytopathogen biocontrol agents, are known to attack the insect cuticle, but their action on the insect gut needs to be better investigated. RESULTS: In the present paper, we performed a biochemical characterisation of a commercial mixture of chitinolytic enzymes derived from Trichoderma viride and analysed its in vitro and in vivo effects on the PM of the silkworm Bombyx mori, a model system among Lepidoptera. We found that these enzymes have significant in vitro effects on the structure and permeability of the PM of this insect. A bioassay supported these results and showed that the oral administration of the mixture causes PM alterations, leading to adverse consequences on larval growth and development, negatively affecting pupal weight and even inducing mortality. CONCLUSIONS: This study provides an integrated experimental approach to evaluate the effects of fungal chitinases on Lepidoptera. The encouraging results obtained herein make us confident about the possible use of fungal chitinases to control lepidopteran pests. © 2015 Society of Chemical Industry